Dynamics and size of cross-linking-induced lipid nanodomains in model membranes - Štefl, Martin; Šachl, Radek; Humpolíčková, Jana; Cebecauer, Marek; Macháň, Radek; Kolářová, Marie; Johansson, Lennart B-Å; Hof, Martin (Biophysical journal, 2012)
Changes of membrane organization upon cross-linking of its components trigger cell signaling response to various exogenous factors. Cross-linking of raft gangliosides GM1 with cholera toxin (CTxB) was shown to cause microscopic phase separation in model membranes, and the CTxB-GM1 complexes forming a minimal lipid raft unit are the subject of ongoing cell membrane research. Yet, those subdiffraction sized rafts have never been described in terms of size and dynamics. By means of two-color z-scan fluorescence correlation spectroscopy, we show that the nanosized domains are formed in model membranes at lower sphingomyelin (Sph) content than needed for the large-scale phase separation and that the CTxB-GM1 complexes are confined in the domains poorly stabilized with Sph. Förster resonance energy transfer together with Monte Carlo modeling of the donor decay response reveal the domain radius of ~8 nm, which increases at higher Sph content. We observed two types of domains behaving differently, which suggests a dual role of the cross-linker: first, local transient condensation of the GM1 molecules compensating for a lack of Sph and second, coalescence of existing nanodomains ending in large-scale phase separation.
Keywords: Lipid Bilayers; Membrane Microdomains; Models, Chemical; G(M1) Ganglioside; Phase Transition; Cholera Toxin; reagencia zkříženě vázaná; lipidové dvojvrstvy; membránové mikrodomény; molekulární modely; molekulární konformace; Models, Molecular; G(M1) gangliosid; fluidita membrány; Membrane Fluidity; Cross-Linking Reagents; Molecular Conformation; cholerový toxin; chemické modely; změna skupenství